The Role Of The Village Sabha In Traditional Village Government - Made Artana, I (International Journal of Educational Research & Social Sciences, 2024)
The dualism of the village government system in Bali is not found anywhere else in Indonesia, the dualism of the village government is the administrative government of the government led by a village head/village head and the customary government led by Bendesa, but each of these governments regulates two different things. In this customary village government, institutions that play a role besides the head of customs/bendesa, there are also other institutions known as the Village Sabha, whose members are community representatives who are sent to become members of this Village Sabha. This Village Sabha has a position in the traditional village and an important role in the traditional village government system.The position of the Village Sabha in the Customary Village Government system in the Gunaksa Traditional Village, Cempaga Bangli Village, does not expressly regulate the existence of the Village Sabha, but its existence is very felt even though the Village Sabha is not expressly regulated in the traditional village awigs of the Village Sabha is equated with the Loka Kerta Sabha in the Gunaksa Traditional Village, Cempaga Bangli Village, which is a complete customary institution in the customary village government system.  The existence of Kerta Loka Sabha is very much needed because it is a partner of traditional villages in the government of traditional villages. The role of the Village Sabha in the Gunaksa Traditional Village, Cempaga Bangli Village as stipulated in the Customary Village Regulation and other regulations has been running for a long time, another name for the Village Sabha with the name Kerta Loka Sabha carries out tasks such as the Village Sabha.  As a partner of the traditional bendesa, it prepares a development program every year with the bendesa.  Kerta Loka Sabha provides advice and supervises the performance of the village, especially those related to the development program that has been determined. Kerta Loka Sabha also carried out the selection of customary villages, in such a way that the role of Kerta Loka Sabha of Gunaksa Traditional Village, Cempaga Bangli Village, so that the traditional village development program has been running and can be felt by indigenous peoples.